Thermoelectric transport coefficients of bulk and low dimensional structures - Muldera, Joselito E. (2006)
Equations for the thermoelectric properties of the three, two-, and one-dimensional free electron gas conductors at constant temperature were derived in this study. The method used herein is a semiclassical approach of transport properties in metals where electronic response is directly proportional to applied fields or temperature gradients in the relaxation time approximation scheme. A key to this linear response formulation is first to determine the density of states of the system under consideration. The density of states describes the distribution of the one-electron energy levels. Knowing the density of states, the wire and well width dependence of the electrical conductivity, thermal conductivity and figure of merit are obtained in the quasi-one-dimensional and two-dimensional case, respectively at constant temperature and variable carrier density. The dependence of these transport properties as well as the thermoelectric power to the system's chemical potential also at constant temperature was shown for all dimensions. For the quasi-one-dimensional system, the effect of varying the chemical potential as a function of temperature at constant carrier density was also studied. It was shown that by changing the size and carrier concentration, the temperature and chemical potential-dependence of the transport properties of a certain material can be controlled so as to obtain high thermoelectric efficiency.